Self-Awareness Research Trends In The Indonesian Journal of Guidance and Counseling - Al Halik; Zamratul Aini; Diana Devi; Teuku Yasser (Universitas Negeri Medan, 2025)
Self-awareness serves as a cornerstone of personal understanding and consciousness. This ability helps individuals to understand themselves and grow into good people. Study This uses analysis content on several articles published in journals, including guidance and counseling/Islamic guidance and counseling throughout Indonesia, with self-awareness as the main focus of the study. This study discloses that several publications focusing on self-awareness show pattern fluctuations, of which 2022 is peak experience enhancement. Among these publications, the most dominant research design is quantitative research. Apart from that, high school students, multicultural awareness and sociodrama techniques are the targets, focus of study and most treatment. In connection with the findings of this study, several recommendations have been proposed for future research that bases self-awareness as the main focus. These recommendations include increasing the diversity of research types and choosing a more varied treatment technique.